Shrub avoidance by an open-adapted ground squirrel in a shrub-encroached environment. - Alexandra D Burnett; John L Koprowski (PLoS ONE, 2024)
Habitat loss and degradation are leading drivers of the widespread decline in wildlife populations, and understanding how wildlife perceive and navigate their environment is useful for predicting responses to future landscape changes. Small mammals play an important role in their environments, however, many species are threatened by rapid environmental change. The Harris' antelope squirrel (Ammospermophilus harrisii) is endemic to the Sonoran Desert but faces multiple landscape changes due to anthropogenic activity. We fitted A. harrisii with radio collars to quantify resource selection and better understand how further environmental change may affect squirrels. Squirrels exhibited differential selection depending on behavior and scale. When selecting for microsites suitable for burrows and alarm calling (i.e., fourth-order selection), squirrels selected for both cacti and shrub portions of the habitat. Overall habitat selection within home ranges (i.e., third-order selection) showed selection against shrub patches, however, suggesting that further shrub encroachment may have consequences for A. harrisii behavior and distribution.